Seed spices enriching basket of foreign exchange - Janakiram, T; Lal, G (Indian Horticulture, 2019)
India is ‘the land of spices’. The glories of Indian spices are known throughout the world. Total 109 spices are listed by ISO and 63 spices are grown in India; out of which 20 are being classified as seed spices. Out of the 20 seed spices, ICAR-NRC on Seed Spices, Ajmer is working on 10 most important seed spices namely cumin, coriander, fennel, fenugreek, ajwain, nigella, dill, anise, celery and caraway. Seed spices are crops whose seed is used for taste and flavour. Seed spices are known as gold in arid and semi-arid areas of India. In India, seed spices are mostly grown in Rajasthan, Gujarat besides Uttar Pradesh, Madhya Pradesh, Punjab, Haryana and some parts of south India. India is the largest producer, consumer and exporter of seed spices in the world. The area under seed spices is about 1.78 million ha and production is about 1.47 million tonnes. India is consistent source of seed spices for importing countries worldwide. There has been ever increasing demand of seed spices and importing countries look at India for quality produce of seed spices. India is exporting only 15% of its production annually and fullfill 50-60% of world demand. The total export of seed spice crops is more than `2,800 crore, out of which cumin alone contributes more than `1,900 crore annually.